Calcification of a Synthetic Renovascular Graft in a Child. (2016) - Chong, D.S.T.; Constantinou, J.; Davis, M.; Hamilton, G.
Abstract : Introduction: Vascular grafts, especially in paediatric cases, need to be durable. Common failures such as thrombosis are well documented with research efforts directed towards them. However, there are lesser known causes of graft failure, such as graft calcification, and these also require further research focus. Report: A paediatric case is described in which a synthetic renovascular graft, implanted for mid-aortic syndrome, became calcified, necessitating surgical intervention to resolve graft malfunction. Significant calcification in the limb of a bifurcated polyethylene terephthalate graft was found to be the cause of resistant stenosis and refractory hypertension. Histology conducted on the explanted limb showed the presence of multinuclear giant cells, indicating a chronic foreign body response. Discussion: Calcification of vascular grafts is probably more common than previously recognised. Stenosis typically resistant to angioplasty may result in the long term and thus leading to surgical intervention. In young children, this is suboptimal as these grafts need to last throughout adulthood. Explanted prosthetic grafts should be sent to specialist registries such as that in Strasbourg to be optimally assessed so that contributory factors can be identified. Highlights: Calcification is found in a renovascular synthetic graft in a paediatric patient. Calcification is a lesser known cause of premature vascular graft failure. Careful consideration of graft material is required, especially in paediatric cases. A registry of vascular graft failures is advocated to identify the causes.